Surgeon Experience and Outcomes in Microsurgical Breast Reconstruction: A 10-Year Single Surgeon Analysis - Rothchild, Evan; Smith, Isabelle T.; Popoola, Stephen O.; Ricci, Joseph A.; Tanna, Neil (Journal of Reconstructive Microsurgery, 2025)
Microsurgical breast reconstruction with deep inferior epigastric perforator (DIEP) flaps has become increasingly popular. While surgeons undergo rigorous training, it is believed that plastic surgeons continue to refine and enhance their performance through independent practice. This study evaluates the effect of surgeon experience on clinical outcomes in DIEP flap breast reconstruction.A retrospective review was conducted on consecutive DIEP flap procedures performed by a single surgeon from fellowship completion in 2013 to 10 years of independent professional practice in 2023. Patients were categorized into “early” and “late” groups, separated by a midpoint surgery date (July 30, 2018). Statistical analyses included student's t-tests, chi-squared analysis with Fisher's exact test, and multivariable regressions controlling for comorbidities.The study included a total of 1,182 DIEP flaps in 632 patients, with 238 in the early group and 394 in the late group. The late group had a lower mean body mass index (28.83 vs. 29.98, p = 0.004), prevalence of hypertension (26.6% vs. 35.3%, p = 0.021), and prevalence of diabetes (7.9% vs. 14.3%, p = 0.010) than the early group. After controlling for potential confounders, the late group was independently associated with decreased length of stay (incidence rate ratio [IRR] = 0.611, p < 0.001) and fewer revision surgeries (IRR = 0.689, p < 0.001).This large, single-surgeon series demonstrates that even with extensive initial training, plastic surgeons continue to evolve their surgical outcomes through accumulated experience. These findings emphasize the importance of consistent volume over time in achieving optimal results in microsurgical breast reconstruction.
Keywords: microsurgical breast reconstruction; surgeon experience; learning curve